PRODUKSI DAN KOMERSIALISASI UDANG VANAMEI SALINITAS RENDAH DI DESA SOKONG, LOMBOK UTARA - Sitti Hilyana; Sadikin Amir; Sahrul Alim; Andre Rachmat Scabra; Nuri Muahiddah; Wastu Ayu Diamahesa (Universitas Mataram, 2023)
Vannamei shrimp production is a popular activity in the field of inland aquaculture. North Lombok Regency has a land area of 809.53 square kilometers, consisting of special areas (protected forests, wildlife areas, and others) covering 361.86 square kilometers (44.30%), while the remaining land is mainly used for agricultural purposes, covering an area of 447.67 square kilometers (55.30%). The water area of North Lombok is 594.71 square kilometers with a coastline length of 127 kilometers. Considering the vast land area, it is expected to contribute to the production of vannamei shrimp, which has so far relied solely on coastal cultivation. This community service aims to provide understanding and enhance the community's ability to manage vannamei shrimp cultivation, particularly in limited spaces far from the coastal areas, and optimize the existing freshwater sources. The method used in this community service is Focus Group Discussion (FGD), which involves providing information and insights to farmers regarding the development of low salinity shrimp cultivation technology in circular ponds using the biofloc method, accompanied by mentoring and practical application. The dissemination of information on the development of low salinity shrimp cultivation technology in circular ponds using the biofloc system has helped farmers in cultivating shrimp in low salinity water using modern technology, namely the biofloc system. This technology has improved and increased the quality and quantity of production in the cultivation partnership with Muda Mandiri in Tanjung Village, Tanjung Subdistrict, North Lombok, West Nusa Tenggara. The dissemination of information on the development of low salinity shrimp cultivation technology in circular ponds using the biofloc system can also assist farmers in improving the quality of the products in the cultivation partnership with Muda Mandiri in Tanjung Village, Tanjung Subdistrict, North Lombok, West Nusa Tenggara.